THE EVALUATION OF FIXED ASSETS BASED ON SAK-ETAP AT PT. AIR MANADO - Halena Ngolo; Jenny Morasa; Robert Lambey (Universitas Sam Ratulangi, 2023)
Abstract: Fixed assets are company assets that have a form, have economic benefits for morethan one year, and are acquired by the Company to carry out company activities, not for resale.Fixed assets are regulated in the Financial Accounting Standards for Entities Without PublicAccountability 15. In SAK ETAP 15, it is explained that fixed assets must be treated based onthe recognition, measurement, depreciation, recognition of recognition, and disclosure of fixedassets. This research aims to evaluate the treatment of fixed assets at PT. Air Manado with theprovisions of SAK ETAP No 15 regarding the applicable fixed assets. This study uses aqualitative descriptive analysis method and research data obtained through interviews anddocumentation. The outcomes showed that the accounting treatment for fixed assets owned bythe Company is recognition that follows SAK ETAP 15, measurements that follow SAK ETAP15, depreciation that follows SAK ETAP 15, recognition that is not following SAK ETAPbecause PT Air does not write off fixed assets that have no useful life and remain in the financialstatements where this does not reflect the actual value of these assets. The disclosure needs tofollow SAK-ETAP No. 15. This is because PT Air Manado did not immediately write off theassets. After all, there needed to be more information obtained by the finance manager fromthe relevant division.